Dissecting the Link Between Tax Crimes and Corruption: A Threats to Economic Stability - Mexi Zwalen (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The paper discusses the complex correlation between tax crime and corruption and its impact on economic stability. Through in-depth analysis, the author explores the links that exist between these both phenomena, identifying how illegitimate tax practices can become a hotbed of corruption at the government level and vice versa. In this context, this article discussed the threats facing economic stability as a consequence of the negative interaction between tax crimes and corruption. It is expected that a better understanding of these dynamics will help authorities design effective policies to protect economic stability and improve the integrity of the tax system. In conclusion, teh paper highlights the need for joint efforts from the government, private sector, and society to prevent and eradicate criminal tax practices and corruption in order to support sustainable economic development.